DEVELOPMENT OF A SYSTEM OF DIGITIZATION AND CATALOGING OF PROTOCOLS OF THE TRAFFIC SAFETY COMMISSION OF THE IVANO-FRANKIVSK CITY-TERRITORIAL COMMUNITY - Pashkovskyi, B. V. (Systems and Technologies, 2024)
The article is devoted to the development of a system of digitization and cataloging of protocols and decisions of the Traffic Safety Commission of the Ivano-Frankivsk City Territorial Community (KBDR). KBDR considers the issue of implementation of measures to ensure improvement works, organization of road traffic and increase the safety of all road users on the territory of Ivano-Frankivsk urban territorial community in accordance with the master plan, projects of detailed planning and construction of settlements, projects of capital repair, reconstruction and new construction of objects of the street and road network, implementation of automated traffic control systems, complex transport schemes and traffic organization schemes, parking zones taking into account the principles of sustainable development and compliance with the rules of landscaping. From 2016 to 2024, the commission held more than a hundred meetings where more than 3,150 issues were considered. Commission protocols are drawn up in the form of PDF files and uploaded to the server. There is an urgent need to find decisions of the commission at a certain address, location, etc. Appeals from citizens, municipal inspection requires the formation of answers and excerpts whether a certain decision was made or not. The article deals with the development of a system for digitizing commission protocols and creating a catalog (a website with a database) with a quick search function. It is possible to download the original protocol to form an official extract. The database was designed and implemented using Microsoft SQL Server with the Entity Framework Core package for storing KBDR solutions. A system for digitizing PDF files of the commission’s decision and importing them into the database has been developed. A web application with a search function was built using ASP .NET Core MVC technology and Razor Views.